Beneficial Effect of Fenofibrate in Combination with Silymarin on Parameters of Hereditary Hypertriglyceridemia-Induced Disorders in an Animal Model of Metabolic Syndrome - Soukop, Jan; Kazdová, Ludmila; Hüttl, Martina; Malínská, Hana; Marková, Irena; Oliyarnyk, Olena; Miklánková, Denisa; Gurská, Soňa; Rácová, Zuzana; Poruba, Martin; Večeřa, Rostislav (Biomedicines, 2025)
Background: Hypertriglyceridemia has serious health risks such as cardiovascular disease, type 2 diabetes mellitus, nephropathy, and others. Fenofibrate is an effective hypolipidemic drug, but its benefits for ameliorating disorders associated with hypertriglyceridemia failed to be proven in clinical trials. Methods: To search for possible causes of this situation and possibilities of their favorable influence, we tested the effect of FF monotherapy and the combination of fenofibrate with silymarin on metabolic disorders in a unique model of hereditary hypertriglyceridemic rats (HHTg). Results: Fenofibrate treatment (100 mg/kg BW/day for four weeks) significantly decreased serum levels of triglyceride, (-77%) and free fatty acids (-29%), the hepatic accumulation of triglycerides, and the expression of genes encoding transcription factors involved in lipid metabolism (Srebf2, Nr1h4. Rxrα, and Slco1a1). In contrast, the hypertriglyceridemia-induced ectopic storage of lipids in muscles, the heart, and kidneys reduced glucose utilization in muscles and was not affected. In addition, fenofibrate reduced the activity of the antioxidant system, including Nrf2 expression (-35%) and increased lipoperoxidation in the liver and, to a lesser extent, in the kidneys and heart. Adding silymarin (micronized form, 600 mg/kg BW/day) to fenofibrate therapy increased the synthesis of glycogen in muscles, (+36%) and reduced hyperinsulinemia (-34%). In the liver, it increased the activity of the antioxidant system, including PON-1 activity and Nrf2 expression, and reduced the formation of lipoperoxides. The beneficial effect of combination therapy on the parameters of oxidative stress and lipoperoxidation was also observed, to a lesser extent, in the heart and kidneys. Conclusions: Our results suggest the potential beneficial use of the combination of FF with SLM in the treatment of hypertriglyceridemia-induced metabolic disorders.
Keywords: glycogen synthesis; silymarin; oxidative stress; metabolic syndrome; fenofibrate; insulin resistance; reesterification of fatty acids; triglycerides